INFLUENCE OF GENETIC AND ENVIRONMENTAL FACTORS ON LACTATION PERFORMANCE OF HOLSTEIN FRIESIAN CATTLE IN BALOCHISTAN - Nawaz; A .; A. H. Nizamani; I. B. Marghazani; Nasrullah; A. Fatih (Journal of Animal and Plant Sciences, 2013)
Data on 100 Holstein-Friesian cows for a period of 15 years (1988-2002) were analyzed using least squares and maximum likelihood methods. Lactation components such as lactation length, peak yield, milk yield and age at calving averaged 319±56, 474±42 liters, 3661±785 liters, 1963±636 days respectively. The h2 estimates were 0.49, 0.29, 0.32 and 0.535 for these parameters, respectively. Seasonal analysis revealed that there was no influence of calving season on lactation components. Summer, Autumn, Winter and Spring had lactation length 323±50, 317±49, 313±56 and 321±55 days, monthly peak yield 477±77, 472±70, 466±53 and 482±73 kg, and milk yield 3685±766, 3593±817, 3645±677, 3724±864 kg., respectively.
Keywords: Genetics; environment; lactation performance; Friesian; Balochistan